2020
DOI: 10.13106/jafeb.2020.vol7.no2.205
|View full text |Cite
|
Sign up to set email alerts
|

Factor Affecting Customers’ Decision to Use Mobile Banking Service: A Case of Thanh Hoa Province, Vietnam

Abstract: The article aims to identify the main factors affecting customers' decision to use mobile banking service in Vietnam, a case study in Thanh Hoa province. Based on theoretical frameworks of the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT), the study has been conducted with 370 questionnaires to consumers who have not yet used and are currently using mobile banking in Thanh Hoa province. The research results indicates that several factors have been evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 13 publications
3
19
0
Order By: Relevance
“…Hedonic aspects result from the aesthetic or emotional feelings such as love, hate, fear, joy, etc. (Ba et al, 2020). In the hedonic view, shopping is a potential source of entertainment and enjoyment resulting from fun and play (Hirschman & Holbrook, 1982).…”
Section: Consumer Motivationmentioning
confidence: 99%
“…Hedonic aspects result from the aesthetic or emotional feelings such as love, hate, fear, joy, etc. (Ba et al, 2020). In the hedonic view, shopping is a potential source of entertainment and enjoyment resulting from fun and play (Hirschman & Holbrook, 1982).…”
Section: Consumer Motivationmentioning
confidence: 99%
“…In particular, previous literature indicated that TAM consistently accounts for 40% of variance in usage intention and behaviors (Venkatesh & Davis, 2000). TAM has been widely examined and validated and is an extensively accepted model in different sorts of technologies related to user and organization acceptance and adoption such as the World Wide Web (Lederer, Maupin, Sena, & Zhuang, 2000;Van der Heijden, 2004;Tahar, Riyadh, Sofyani, & Purnomo, 2020), Intranet (Horton, Buck, Waterson, & Clegg, 2001), E-commerce (Olson & Boyer, 2003;Pavlou, 2003;Han, Thao Nguyen, & Nguyen, 2016), Internet Banking (Aldás-Manzano, Lassala-Navarré, Ruiz-Mafé, & Sanz-Blas, 2009, Mobile banking (Le, Trinh, & Nguyen, 2020;Phuong, Luan, Dong, & Khanh, 2020) that lead to their widespread acceptance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Banking service is provided by a bank that allows its customers to conduct banking transactions (Le et al, 2020). Behavioral intention (BI) is described as a broad engagement of a client with a contemporary product or service that a person will consistently use in the future (Lai et al, 2019;Oliver, 2014).…”
Section: Introductionmentioning
confidence: 99%